2022
DOI: 10.2217/pme-2021-0128
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Instability Testing in Colorectal Patients with Lynch Syndrome: Lessons Learned from a Case Report and How to Avoid Such Pitfalls

Abstract: We present the case of a patient with Lynch syndrome and metastatic colorectal carcinoma (mCRC). The initial immunohistochemistry (IHC) test for deficient mismatch repair gave a false negative result. However, the same mutation has accurately has been detected with IHC in other cancers with microsatellite instability (MSI) This supports the determining role of somatic missense mutations in MMR IHC. MSI-PCR testing confirmed MSI and the patient benefited from nivolumab with a complete metabolic response. We ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 38 publications
0
32
0
Order By: Relevance
“…However, not all centers in Korea have adopted universal screening using the tumor IHC/MSI test due to insurance issues. Although MSI testing has the potential to be integrated into NGS testing in the future, at the current developmental stage, several technical difficulties are still associated with MSI testing [ 16 ]. Thus, an up-front NGS test may be more cost-effective than a step-by-step universal screening test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, not all centers in Korea have adopted universal screening using the tumor IHC/MSI test due to insurance issues. Although MSI testing has the potential to be integrated into NGS testing in the future, at the current developmental stage, several technical difficulties are still associated with MSI testing [ 16 ]. Thus, an up-front NGS test may be more cost-effective than a step-by-step universal screening test.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all centers have adopted “universal tumor screening”, and Amsterdam II criteria are very stringent, such that they miss as many as 68% of patients with LS [ 15 ]. With respect to the MSI test, at the current level of development, there are challenges with utilizing the MSI test due to biological and technical heterogeneity [ 16 ]. Meanwhile, the advent of next generation sequencing (NGS) tests, which allow the cost-effective analysis of multiple genes simultaneously, and the resulting development of multigene panels have allowed low-cost genetic testing of individuals with a risk of developing hereditary cancers.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that screening for defective DNA mismatch repair using immunohistochemistry and/or microsatellite instability tests still poses many challenges due to difficulties in distilling the biological and technical heterogeneity of microsatellite instability testing into usable data. It has been reported that immunohistochemistry testing of the mismatch repair machinery may give different results for a given germline mutation which suggests the role of somatic missense mutations in mismatch repair immunohistochemistry (21). Nevertheless, although this personalized approach to treat refractory mCRC can be used in a certain subset of patients, currently the only FDA-approved standardized treatment strategy for mCRC beyond the second line is the use of regorafenib or the combined agent trifluridine/tipiracil (19).…”
Section: Discussionmentioning
confidence: 99%
“…MMR reduces DNA errors 100–1000 fold, and prevents them from becoming fixed mutations during cellular proliferation [ 42 , 43 ]. The role of MMR defects in the development of cancer was first established when mutation in MSH2 was linked to hereditary nonpolyposis colorectal cancer, also known as Lynch syndrome [ 44 ]. Over time, the MMR genes MLH1 , MSH2 , MSH6 , and PMS2 were associated to an autosomal dominant, hereditary predisposition to colon cancer.…”
Section: Molecular Landscapementioning
confidence: 99%